(untitled) (Global Conference on Medical and Health Sciences, 2026)
Radical surgical resection remains the cornerstone of curative treatment for locally advanced gastric cancer (LAGC). However, the optimal extent of surgical resection remains controversial, particularly in patients with advanced local tumor invasion. The choice between total gastrectomy, subtotal gastrectomy, and combined multivisceral resections may significantly influence both postoperative outcomes and long-term survival. Although TNM stage remains the principal prognostic indicator, accumulating evidence suggests that the extent and radicality of surgical treatment play an equally important role in achieving durable oncological control. Evaluation of long-term outcomes following different types of radical surgical procedures is therefore essential for optimizing treatment strategies and improving survival in patients with LAGC.